Press-fit reverse shoulder arthroplasty in case of advanced humeral bone loss – Is additional distal fixation necessary for primary stability?. (February 2021) - Jahnke, Alexander; Müller, Felizia; Fonseca Ulloa, Carlos A.; Rickert, Markus; Werner, Birgit S.; Gohlke, Frank
Abstract: Background: Revision reverse shoulder arthroplasty (RSA) poses considerable surgical challenges. We hypothesized that a newly developed press-fit stem, which is modeled on the medullary canal of the supracondylar region of the distal humerus by a slight distal bend, achieve both correct fit and sufficient primary stability and that additional distal fixation by interlocking screws is favorable in case of advanced humeral bone loss. Methods: A modular tapered press-fit stem was implanted in 16 Sawbone humeri in three consecutively created defect situations (200 mm (experimental group type 3°), 160 mm (type 4°) and 120 mm (type 5°) bone length above the epicondylar line. In experimental groups type 4° and 5°, additional distal interlocking screw fixation with one to three screws was tested. Primary stability was investigated by measuring micromotions with a high-precision rotational setup. Findings: Highest relative micromotions were noted at the proximal end in experimental groups type 3° and type 4°, whereas in type 5° highest micromotions could be seen at the distal end. Overall micromotions were significantly lower in type 3° and increased with extended defect size. In experimental group type 5°, micromotions increased with reduced additional distal screw fixation. Interpretation: The examined press-fit stem did not provide sufficient primary rotational stability in all constructs without additional support. Advanced distal humeral bone loss had a strong impact on primary fixation. In experimental group type 5° with 120 mm bone remaining, it might be beneficial to use three distal interlocking screws in the supracondylar region in order to neutralize torque and to avoid early loosening. Highlights: Revision reverse shoulder arthroplasty poses surgical challenges. Distal interlocking screws are favorable in case of advanced humeral bone loss. Three defect situations (types 3°, 4° and 5°) were analyzed. Micromotions were lower in type 3° and increased with extended defect size. It might be beneficial to use at least two screws with type 5° defect.